Hadith #4638 - Sahih Muslim - Junadah bin Abi Umayya (Sahih Muslim)
We called upon ‘Ubada b. Samit who was ill and said to him: May God give you health I Narrate to us a tradition which God may prove beneficial (to us) and which you have heard from the Messenger of Allah (ﷺ). He said: The Messenger of Allah (ﷺ) called us and we took the oath of allegiance to him. Among the injunctions he made binding upon us was: Listening and obedience (to the Amir) in our pleasure and displeasure, in our adversity and prosperity, even when somebody is given preference ov
Grade: Sahih